Fibra de curauá como reforço em matriz cimentícia para fabricação de telhas e placas de fibrocimento - SALES, Cintia Gama (Universidade Federal do Pará, 2017)
Natural fibers such as reinforcing fragile matrices based on cementitious materials, have attracted great interest in developing countries, because of its low cost, availability, energy saving. The use of composites in plates, roof tiles and prefabricated components, can make a significant contribution to the rapid growth of infrastructure in developing countries. Among the natural fibers, curauá fiber, Ananas erectifolius, has gained prominence because of its high tensile strength. The main objective of this work is the use of curauá fiber as reinforcement matrix with Portland cement, for use in structural elements such as slabs and tiles. For this study, testing and compression modulus of elasticity in mixtures with a volume fraction of 1% and 2.5% and fiber length of 1 cm and 2 cm, and full mortar without fibers were performed. The mixture showed the best results in terms of workability, was the volumetric fraction of 1% and 1 cm fiber length, was chosen for the manufacture of cement tiles and plates. For the evaluation of composites was conducted tensile strength test in bending the plates and tiles with curauá fibers and no fibers, for comparison. The results confirmed the influence of the fibers on the composite deformation capacity increasing by 46% the tensile strength in plate bending with curauá fiber relative to the plate without fiber, and increased tile breaking load of 49% with respect to tile without fiber.